NONSEPARABLE SPACE-TIME COVARIANCE MODELS: SOME PARAMETRIC FAMILIES - De Iaco S.; Myers D.E.; Posa D. (My University, 2002)
By extending the product and product-sum space-time covariance models, new families are generated as integrated products and product-sums. These include nonintegrable space-time covariance models not obtainable by the Cressie-Huang representation. It is shown how to fit the spatial and temporal components of the models as well as the probability density function. The methods are illustrated by a case study.
Keywords: PRODUCT-SUM MODELS; INTEGRATED MODELS; SEPARABILITY; ADMISSIBILITY